Benign paroxysmal positional vertigo and vestibular myogenic evoked potential - Rossetto, Ana Paula; Franciozi, Camila; Zen, Paulo Ricardo Gazzola; Sleifer, Pricila (Seven Editora, 2024)
Benign Paroxysmal Positional Vertigo (BPPV) is considered a common disorder of the vestibular system. It corresponds to a hydro-mechanical disorder of the inner ear caused by abnormal stimulation of the dome of one or more of the three semicircular canals. BPPV represents approximately 25% of all vertigo of vestibular origin, it can manifest itself at any age, but it is more frequent after the age of 60. BPPV is known to be explained by the migration of otoconia from the utricle macula to the semicircular canals. The definitive diagnosis requires the performance of specific positional maneuvers, and the findings include: latency, direction, and duration of positional nystagmus. The vestibular myogenic evoked potential (VEMP) is a myogenic response evoked by brief pulses of sound and can be used as a complementary test for otoneurological evaluation, presenting several clinical applications in the diagnosis and follow-up of various vestibular diseases, including BPPV. DOI:https://doi.org/10.56238/sevened2024.001-043